Quality, chilling injury, and antioxidant enzyme activities of Carica papaya L. cv. 'frangi' after hot water treatment and storage - Shadmani, Nasim (2013)
The newly introduced ‘Frangi’ papaya (Carica papaya L.) fruits are in demand worldwide. The fruits are highly perishable and susceptible to chilling injury and insect pest and disease infestations. Currently, there is a demand to reduce postharvest chemical insecticides and fungicides by using safe physical treatments such as heat treatments. Double-dip hot water treatment (hot water dip) has the potential to meet the abovementioned demands for many countries. In addition, an optimum storage temperature may provide fresh and high quality papaya, despite the long transportation duration. There is a need to apply cost effective, sustainable and safe postharvest methods to extend storage and shelf life of the papaya fruits. The objectives of this study were to investigate the effect of heat treatment and storage temperatures on postharvest quality characteristics, chilling injury, peel electrolyte leakage and antioxidant enzyme activities of Frangi papaya during three weeks of storage. The experiment was conducted using a randomized complete block design (RCBD), in a factorial arrangements of treatments (2 heat treatment levels x 2 storage temperatures x 4 storage duration), with three replications of three fruits per replication. The fruits were double-dipped in hot water (30 min at 42 °C, 20 min at 49 °C) and stored at 6 and 12 °C for three weeks. Non hot water dip fruits acted as the control treatment. Physical and chemical quality characteristics, such as fruit color, weight loss, firmness, titratable acidity, pH, ascorbic acid, soluble solids concentration, and ethylene and carbon dioxide production rates, were measured at weekly intervals for three weeks. Chilling injury, peel electrolyte leakage and antioxidant enzymes (catalase, ascorbate peroxidase and superoxide dismutase) activities were also determined at weekly intervals during the three weeks of storage. The fruit quality characteristics such as color values, titratable acidity, ascorbic acid and soluble solids concentration were not significantly affected by double-dip hot water treatment. Treated fruits had a lower weight loss and higher firmness after week 2 of storage compared with control fruits. Ethylene production rate fluctuated during storage and was not inhibited by hot water dip at week 1 of storage. Fruits stored at 12 °C showed lower firmness and higher weight loss but normal peel colour progression compared to fruits stored at 6 °C. Inhibition of the normal ripening processes during the three weeks of storage at 6 °C was evidenced by the high pulp firmness and impaired peel color progression. Double-dip hot water treatment alleviated the Frangi papaya chilling injury incidence. Peel and pulp chilling injury incidence were affected by hot water treatment. However, at weeks 1 and 2 of storage, peel chilling injury incidence was higher in hot water dip fruits compared with control fruits. The peel electrolyte leakage percentage of heat treated samples was significantly lower than control fruits. Hot water dip fruits which were stored at 6 °C had significantly lower peel chilling injury incidence than control fruits. It could be concluded that hot water dip was capable of reducing peel chilling injury at 6 °C storage. The fruits characteristics at the molecular level were monitored at optimum storage temperature (12 °C) and chilling temperature (6 °C). Peel electrolyte leakage was significantly and positively correlated with catalase activity. The increase in peel chilling injury incidence resulted in the increase of catalase activity which functions to reduce the active oxygen species. The catalase activity was lower in treated fruits and a significant increase in catalase activity was observed in control fruits during week 2 of the storage. Ascorbate peroxidase activity was higher in hot water dip fruits. Similarly hot water dip fruits stored at 12 °C had higher ascorbate peroxidase activity compared with control fruits. Frangi papaya stored at 12 °C during three weeks storage showed higher superoxide dismutase activity than 6 °C. The results of the present study are indicative of the fruits’ active antioxidant defense mechanism in response to hot water dip. Thus, by the application of hot water dip on Frangi papaya, it is possible to capture a greater share of the international market and simultaneously maintain the fruits quality characteristics, extend storage life and reduce peel and pulp chilling injury during a long storage period. As hot water dip is a physical treatment, the processes involved are environment friendly while fruits produced are safe for consumption.